2008
DOI: 10.1021/ct800155q
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate and Transferable Intermolecular Diatomic Hydrogen Potential for Condensed Phase Simulation

Abstract: An anisotropic many-body H2 potential energy function has been developed for use in heterogeneous systems. The intermolecular potential has been derived from first principles and expressed in a form that is readily transferred to exogenous systems, e.g. in modeling H2 sorption in solid-state materials. Explicit many-body polarization effects, known to be important in simulating hydrogen at high density, are incorporated. The analytic form of the potential energy function is suitable for methods of statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
178
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 91 publications
(182 citation statements)
references
References 44 publications
3
178
0
1
Order By: Relevance
“…Note, the experimental isotherms that are shown in Figure 3(a) were estimated from reference 11. The H 2 potential used in this work is a five-site polarizable model that was developed from first principles previously by Belof et al 78 It can be seen that simulations using this model generated an isotherm that is in very good agreement with experiment at 77 K. The calculated hydrogen sorption isotherm and the experimental isotherm at 77 K are nearly equivalent to within joint uncertainties (the maximum calculated error is ±0.04 wt %). The greatest deviation between experiment and simulation at 77 K can be observed at pressures lower than 0.20 atm, where simulation slightly oversorbs experiment.…”
Section: B Many-body Polarizationmentioning
confidence: 59%
“…Note, the experimental isotherms that are shown in Figure 3(a) were estimated from reference 11. The H 2 potential used in this work is a five-site polarizable model that was developed from first principles previously by Belof et al 78 It can be seen that simulations using this model generated an isotherm that is in very good agreement with experiment at 77 K. The calculated hydrogen sorption isotherm and the experimental isotherm at 77 K are nearly equivalent to within joint uncertainties (the maximum calculated error is ±0.04 wt %). The greatest deviation between experiment and simulation at 77 K can be observed at pressures lower than 0.20 atm, where simulation slightly oversorbs experiment.…”
Section: B Many-body Polarizationmentioning
confidence: 59%
“…These were calculated using the Lennard-Jones 12-6 potential, partial charges with Ewald summation, 41 50 and the fivesite polarizable model also developed by Belof et al 50 These models are denoted Buch, DL, BSS, and BSSP, respectively. The simulated results are presented for the polarizable potential; however, the simulated H 2 sorption isotherms and Q st values for the other models in both ZIFs are discussed where appropriate, with data shown in the Supporting Information ( Figures S6 and S12).…”
Section: B Theoretical Sectionmentioning
confidence: 99%
“…32 Additionally, it will be shown that the rotational barrier for H 2 at the most favorable sorption site in [Zn(trz)(tftph)] is among the highest of reported MOF materials based on INS measurements and calculations. 45 For simulations using the BSSP model, polarization was included explicitly in the simulations via a Thole-Applequist type model. [46][47][48] All simulations were performed in the rigid 2 × 2 × 2 system cell of the MOF as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%